POSITION OF LAND EXAMINATION BY JUDGES IN ADMINISTRATIVE COURTS OVER LAND CERTIFICATE DISPUTES - Harahap, Hasanul Raya; Isnawati; Asyari, Fatimah; Putri, Dina Paramitha Hefni (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
Land certificate disputes are a frequent legal issue in Indonesia, in line with the increasing demand for land, its high economic value, and the position of certificates as legal evidence of ownership rights and the object of state administrative decisions. Various problems such as overlapping certificates, administrative errors, and overlapping authority between the State Administrative Court (PTUN) and the District Court, often give rise to legal uncertainty and have implications for social unrest in society. Therefore, this study focuses on a juridical-normative analysis of the role and authority of PTUN judges in examining and deciding cases related to land certificate disputes. The results show that PTUN judges play a strategic role as testers of the legality of land administration decisions, guarantors of legal certainty, and protectors of community rights through judicial oversight mechanisms. On-site inspections by judges are crucial as an effort to objectify field facts and enforce the principle of legality. This study emphasizes the need for regulatory synergy and increased integrity of the land bureaucracy so that legal protection and substantive justice for land rights are truly realized.